Fabrication of TiVO4 photoelectrode for photoelectrochemical application. Issue 53 (2nd December 2022) - Alruwaili, Manal; Roy, Anurag; Nundy, Srijita; Tahir, Asif Ali
Abstract : TiVO4 photoanode was prepared using the spray pyrolysis technique and further employed for photoelectrochemical water splitting to produce hydrogen. Abstract : Photoelectrochemical (PEC) water splitting is one of the promising, environmentally friendly, carbon emission-free strategies for the cost-effective production of hydrogen. The interest in developing effective approaches for solar-to-hydrogen production with stable and visible light active semiconductors directed many researchers to develop stable and efficient materials. For the first time, a nanostructured TiVO4 photoanode was fabricated at a substrate temperature of 250 °C and further annealed at 600 °C using the spray pyrolysis technique and it obtained an optical band gap of ∼2.18 eV. The photoanode underwent photoelectrochemical testing, where it exhibited a high photocurrent density of 0.080 mA cm −2 at 1.23 V ( vs. reversible hydrogen electrode), which can be stable up to 110 min. Further, various physicochemical characterizations were employed to understand the phase purity and thin film growth mechanism. A systematic substrate and annealed temperatures were monitored during the fabrication process. The transmission electron microscopy (TEM) studies revealed agglomeration of TiVO4 nanoparticles with an average size of ∼100 nm accompanying dendritic orientation at the outer edge. This study envisages the design and development of a novel photocatalyst for water splitting under visible light irradiation, an ideal route to a cost-effective, large-scale, sustainable route for hydrogen production.